2017
DOI: 10.18632/oncotarget.23343
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms of long non-coding RNA HOTAIR with breast cancer susceptibility and clinical outcomes for a southeast Chinese Han population

Abstract: Hox transcript antisense intergenic RNA (HOTAIR) is a well-known long non-coding RNA (lncRNA) which participates in tumorigenesis and progress of multiple cancers. However, the associations among polymorphisms on HOTAIR, breast cancer (BC) susceptibility and clinical outcomes have remained obscure. In this case-control study, we assessed the interaction between three lncRNA HOTAIR single nucleotide polymorphisms (SNPs) (rs1899663, rs4759314 and rs7958904) on the risk and clinical outcome of breast cancer in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 53 publications
1
39
0
Order By: Relevance
“…In breast cancer, it works as a predictive marker for metastatic progression and overall survival in early‐stage surgically resected tumors . Of note, emerging studies on the susceptibility of breast cancer have indicated the genetic polymorphisms of HOTAIR . HOTAIR acts as a scaffold in a chromatin‐repressive mechanism.…”
Section: Tumor Driversmentioning
confidence: 99%
“…In breast cancer, it works as a predictive marker for metastatic progression and overall survival in early‐stage surgically resected tumors . Of note, emerging studies on the susceptibility of breast cancer have indicated the genetic polymorphisms of HOTAIR . HOTAIR acts as a scaffold in a chromatin‐repressive mechanism.…”
Section: Tumor Driversmentioning
confidence: 99%
“…Five studies [14][15][16]18,20 Figure S4; Figure 4). A subgroup analysis based on the genotyping method and ethnicity are shown in the Supporting Information Figures S5 and S6.…”
Section: Hotair Polymorphism Rs1899663 and Bc CC And Ocmentioning
confidence: 99%
“…SNPs within the lncRNA H19 have been found to have an increased risk of hepatocellular [61] and gastric cancer [72]. The lncRNA HOTAIR (HOX Transcript Antisense Intergenic RNA) has multiple SNPs associated with an increased risk of several cancer types [69,70,74,75]. These SNPs may affect the expression of the lncRNA or affect its secondary structure [67,73] which alters its canonical function in the cell [76].…”
Section: Lncrnas and Hiv-1 Susceptibilitymentioning
confidence: 99%